2017
DOI: 10.1080/09638237.2017.1340623
|View full text |Cite
|
Sign up to set email alerts
|

Switched on or switched off? A survey of mobile, computer and Internet use in a community mental health rehabilitation sample

Abstract: Community mental health rehabilitation service-users risk finding themselves excluded by a "digital divide". Action is needed to ensure equal access to online opportunities, including healthcare innovations. Clinical and policy implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
1
24
2
Order By: Relevance
“…Depp et al [ 10 ] conducted a survey of CP patients and found that these patients had substantial cognitive and functional deficits and that high punctuations in these impairments were related to the less use of technology. Moreover, in 2014, the National Alliance on Mental Illness (NAMI) [ 11 ] showed that 54% of American patients with schizophrenia owned a mobile phone compared with 64% of the general American population [ 12 ]; similar results have been shown in other studies [ 13 ]. However, recent studies have shown that these rates have changed and that the access of these patients to technology is similar to that of the general population at the moment [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 54%
“…Depp et al [ 10 ] conducted a survey of CP patients and found that these patients had substantial cognitive and functional deficits and that high punctuations in these impairments were related to the less use of technology. Moreover, in 2014, the National Alliance on Mental Illness (NAMI) [ 11 ] showed that 54% of American patients with schizophrenia owned a mobile phone compared with 64% of the general American population [ 12 ]; similar results have been shown in other studies [ 13 ]. However, recent studies have shown that these rates have changed and that the access of these patients to technology is similar to that of the general population at the moment [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 54%
“…Variables that are known to be associated with mental health and that might potentially confound the relationship between mental health and internet access were adjusted in the analysis [ 21 , 22 ]. These include sex, age, partner status, any children under 15 years old in the household, employment status, annual household gross income, financial hardship, and residential remoteness.…”
Section: Methodsmentioning
confidence: 99%
“…They also found that for people with psychosis, those digitally excluded tended to be older and have been in contact with mental health services for a longer period. In contrast, Tobitt and Percival [ 22 ] interviewed 97 users of community mental health rehabilitation services in London and found high levels of digital exclusion. Only 14.4% of their sample used the internet, 17.5% used computers, and 40.2% used mobile phones.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys conducted in the United Kingdom and the United States indicate that digital exclusion is more prevalent among those with mental health difficulties compared with those without [18,19]. Globally, numerous social determinants of health are associated with poorer mental health, including indicators of lower socioeconomic status such as poverty and employment status [20,21].…”
Section: Introductionmentioning
confidence: 99%